Perceptions of social studies teachers and fourth year students on social studies instruction in Isabela School of Arts and Trades - Soriano, Eligio Bautista (1978)
This is a study on the perceptions of social studies teachers and fourth year students on social studies instruction in the Isabela School of Arts and Trades in relation to the other academic subjects. 177 male and female seniors were used as student-respondents and 6 secondary teachers of the discipline as teacher-respondents. The researcher relied on the normative-descriptive survey in gathering facts. The study revealed that none of the teachers has undertaken preservice training in the "new" social studies. There is a need for the administrator to continue his Faculty Development Program to upgrade the educational qualifications and teaching competencies of social studies teachers especially along the teaching of the "new" social studies.